Supplemental Fertilizer Application in the BMP Era for Vegetable Crops Grown in Florida in the BMP Era - Eric Simonne; George Hochmuth (EDIS, 2003)
This publication is one of a series entitled Fertilizer and Irrigation Management in the BMP Era. This series is divided into nine principles described in the Introduction Chapter (HOS-897). This publication is part of Principle 3, "Monitor Crop Nutritional Status and Discover How Healthy the Plants Are." BMP implementation requires a global approach to production management. However, for presentation purposes, each aspect of vegetable production is described in a separate publication. This document is HS906, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: January 2003.